Seating design in the waiting area of specialist clinic in Public Hospital in Malaysia / Diyana Naziha Nor Azman - Nor Azman, Diyana Naziha (2021)
The chair's design and use have received a lot of attention, especially regarding workplace use. Outside of the workplace, it appears that postures have not been properly examined. The chair is regarded to be necessary for dealing with and distributing pressures throughout the body while sitting. This apprehension about sitting turns out to be justified, as prolonged sitting may increase the risk of back damage. (Smidt, G.L. 1994). This study took place at a different hospital from the one used in the initial case study. As a result, the purpose of this study is to investigate and analyze user satisfaction with seating design in a specialty clinic waiting room at a public hospital in Pulau Pinang, Malaysia. The problem that can be stated were the poor seating design in the waiting area in one of the specialist clinic in public healthcare in Penang. (Fauziah I., Wan Mariah and Muna Hanim, 2010). Furthermore, this research aim is to investigate and analyze the user’s satisfaction on seating design when using the waiting area. This research is based on data obtained from the survey questionnaire by user of waiting area. The data was analyzed to investigate the seating design and circulation for waiting area and identify the user satisfaction. The result of this study also suggest that the seating design in the waiting area of specialist clinic is need to be considered for improvement. Because health care is a place where people receive treatment, it must be damaging if they have difficulty navigating the facilities there. These findings provide useful information for hospital planners and facility managers planning future investments in hospital waiting for spaces, resulting in positive patient and employee experiences.